Marylin : a novel of passing - Rundt, Arthur, 1881-1939 (Studies in German Literature Linguistics and Culture Ser., 2022)
Offers a European view of racial attitudes in the US during the era of the Harlem Renaissance and Jim Crow, with relevance to today's Black Lives Matter and #MeToo movements.